The impact of the microbial load of genital mycoplasmas and gestational age on the intensity of intraamniotic inflammation - Kacerovsky, Marian; Pliskova, Lenka; Bolehovska, Radka; Skogstrand, Kristin; Hougaard, David M; Tsiartas, Panagiotis; Jacobsson, Bo (American journal of obstetrics and gynecology, 2012)
OBJECTIVE: The objective of the study was to determine whether the bacterial load of genital mycoplasmas and gestation age are related to intraamniotic inflammatory response using the amniotic fluid levels of 18 inflammatory mediators. STUDY DESIGN: A prospective study of 145 women with singleton pregnancies complicated by preterm prelabor rupture of membranes between 24(0/7) and 36(6/7) weeks was conducted. Amniotic fluid was obtained from all women by transabdominal amniocentesis. The amounts of genital mycoplasma deoxyribonucleic acid were determined using the threshold cycle value and relative and absolute quantification techniques. A panel of multiple proteins was analyzed simultaneously using multiplex technology. RESULTS: Twenty-four women with the presence of genital mycoplasmas in amniotic fluid were included in the final analyses. The concentrations of 9 of the 18 evaluated proteins in the amniotic fluid correlated with bacterial load of genital mycoplasmas independent of the quantification technique used. CONCLUSION: The intensity of intraamniotic inflammatory response to genital mycoplasmas decreased with gestational age.
Keywords: mykoplazmové infekce; bakteriální nálož; stupeň závažnosti nemoci; DNA, Bacterial; Fetal Membranes, Premature Rupture; Pregnancy Complications, Infectious; těhotenství; mediátory zánětu; Mycoplasma Infections; Bacterial Load; plodová voda; Gestational Age; Amniocentesis; amniocentéza; Prospective Studies; Adult; mladý dospělý; Inflammation Mediators; DNA bakterií; Amniotic Fluid; gestační stáří; infekční komplikace v těhotenství; Young Adult; ženské pohlaví; Humans; prospektivní studie; Pregnancy; předčasný odtok plodové vody; chorioamnionitida; dospělí; Chorioamnionitis; Female; Severity of Illness Index; lidé